10-ЛЕТНИЙ ОПЫТ ПРИМЕНЕНИЯ ЭТАНЕРЦЕПТА В УСЛОВИЯХ ФЕДЕРАЛЬНОГО ЦЕНТРА У ПАЦИЕНТОВ С ЮВЕНИЛЬНЫМ АРТРИТОМ - Клавденкова, В А; Лобачева, А В; Белозеров, К Е; Яковлев, А А; Костик, М М; Гайдар, Е В (FORCIPE, 2022)